The role of estrogen in the control of rat osteocyte apoptosis. - Tomkinson, A; Gevers, E; Wit, J; Reeve, J; Noble, B (1998)
We have previously shown that estrogen withdrawal by gonadotrophin-releasing hormone analogs (GnRHa) induces osteocyte death via apoptosis in human bone. Although it is likely that the increase in osteocyte death via apoptosis was related to the loss of estrogen, these experiments could not rule out a direct role for the GnRHa. Therefore, in this study, we have used a rat model of ovariectomy (OVX) to determine whether the effect of estrogen withdrawal extends to other species and to clarify the role of estrogen in the maintenance of osteocyte viability. Twelve 9-week-old rats were divided into three treatment groups: sham operated (SHAM) (n = 4), OVX (n = 4), and OVX + estrogen (E2) (25 microg/day) (n = 4). At 3 weeks following the start of treatment, tibial bones were removed. The percentage of osteocytes displaying DNA breaks, using an in situ nick-translation method, was significantly higher in the OVX group compared with the SHAM control in both cortical bone (10.04% vs. 2.31%, respectively; p < 0.0001) and trabecular bone (6.44% vs. 1.58%, respectively; p = 0.003). Addition of estrogen in the OVX animals completely abrogated the increase in osteocyte apoptosis in cortical bone (0.78%) and trabecular bone (1.17%). The percentage of apoptotic osteocytes decreased with increasing distance from the primary/secondary spongiosa interface below the growth plate in the OVX model and the OVX + E2 model. Nuclear morphology and electrophoresis of DNA confirmed the presence of apoptotic cells in the samples. In conclusion, OVX in the rat results in an increase in osteocyte apoptosis as a direct or indirect result of E2 loss. Addition of estrogen in the OVX animals prevents this increase in osteocyte apoptosis. These data confirm an important role for estrogen in the control of osteocyte apoptosis and the maintenance of osteocyte viability. Estrogen deficiency might, through compromising the viability of osteocyte networks, reduce the ability of bone to respond appropriately to loading.